Kesehatan Mental Sebagai Faktor Penghambat atau Pendukung Proses Belajar Siswa: Kajian Literatur - Baharuddin, Baharuddin (Jurusan Tarbiyah STAI Al-Gazali Bone, 2024)
This research intends to explore the link between mental well-being and learning. By reviewing existing literature, this research will pinpoint mental health issues that influence the learning experience, along with actions that can be taken to enhance students' mental wellness and consequently boost academic success. The findings of the review indicate that mental well-being has a major impact on the learning experience. Mental health challenges like anxiety and depression can obstruct students' focus, drive, and academic success. On the other hand, positive mental health can enhance students' ability to learn and reach their goals. This research concludes that there is a need for more dedicated efforts to support students' mental well-being, at the school, family, and community levels.